Semantic differences of numerical phraseology in Karakalpak and English languages (Eurasian Journal of Learning and Academic Teaching, 2024)
This article focuses on investigating category of number in the English and Karakalpak languages as one of the grammatical categories of the language. Nowadays the comparative-contrastive studies have become more topical in modern linguistics. The linguistic features of singularity and plurality in the angles of expression and content features have been not investigated enough in the English and Karakalpak languages.In this article, the numerical differences of the words in English and Karakalpak languages are analyzed.